Intelectuais e modernidade: Marshall Berman e seu público brasileiro (Revista Brasileira de Ciência Política, 2012)
ResumoA recepção no Brasil ao livro de Marshall Berman, Tudo que é sólido desmancha no ar, ajuda a compreender o entrelaçamento entre o campo intelectual e a indústria cultural, bem como as relações entre o mercado e o pensamento de esquerda nos anos 1980. O sucesso da obra pode ser explicado por uma conjunção de fatores, desde o investimento editorial inovador no mercado, até a predisposição para recebê-la nos meios intelectualizados, em plena transição da ditadura para a democracia. Mudava o lugar do intelectual na sociedade brasileira, em meio a redefinições também no pensamento e na prática de esquerda.Palavras-chave: modernidade; intelectuais; anos 1980; indústria cultural brasileira; individualidade, engajamento político.AbstractThe article analyses the extraordinary reception in Brazil of Marshall Berman´s book about modernism, modernity and modernization, All that is solid melts into air. 34.000 copies were sold in only 12 months after its Brazilian edition of 1986. Till our days 74.500 copies of the book were published, which is a huge number for Brazilian standards. Berman´s audience in Brazil testifies the relation between intellectual field and cultural industry, as well as the links between market and leftwing thought in the eighties. The success of the book can be explained by a series of factors, from the innovating editorial investment to the predisposition to accept it by intellectuals and artists in a particular moment, when the country was facing the transition from dictatorship to democracy. The place of artists and intellectuals was changing in Brazilian society, as was their political commitment.Key words: modernity; intellectuals; eighties; cultural industry in Brazil; individuality; political commitment.